THE COST-EFFECTIVENESS OF PATIENT CONTROLLED ANALGESIA VERSUS ROUTINE CARE IN PATIENTS PRESENTING TO THE EMERGENCY DEPARTMENT IN PAIN, WHO ARE SUBSEQUENTLY ADMITTED TO HOSPITAL. Issue 12 (18th November 2016) - Smith, JE; Squire, R; Pritchard, C; Ewings, P; Barton, A; Rockett, M; Creanor, S; Hayward, C; Eyre, V; Cocking, L; Benger, J
Abstract : Objectives & Background: The clinical effectiveness of patient controlled analgesia (PCA) has been demonstrated in a variety of settings. However, PCA is rarely utilized in the emergency department (ED). The aim of this study was to compare the cost effectiveness of PCA versus treatment as usual (TAU) in patients admitted to the ward from the ED with pain due to traumatic injury or non-traumatic abdominal pain. This is the cost-effectiveness analysis of the previously reported PAin SoluTions In the Emergency Setting (PASTIES) study. Methods: Pain scores were measured hourly for 12 hours using a visual analogue scale from 0–100 mm. Scores of 45 mm or above reflected moderate or severe pain. Cost-effectiveness is reported as the additional cost per hour in moderate to severe pain avoided by using PCA rather than TAU, the incremental cost-effectiveness ratio (ICER). Sampling variation was estimated using bootstrap methods and the effects of parameter uncertainty explored in a sensitivity analysis. Results: For patients suffering pain from traumatic injuries, the cost per hour in moderate or severe pain averted (ICER) was estimated as £24.77 (bootstrap estimate 95% CI=£8.72 to £89.17). The ICER for patients with abdominal pain was estimated as £15.17 (bootstrap estimate 95% CI=£9.03 to £46.00). Overall costs were higher with PCA than TAU in both groups: for pain from traumatic injuries an additional £18.58 (95% CI 15.81 to 21.35) per 12 hours; for abdominal pain £20.18 (95% CI 19.45 to 20.84). Conclusion: The cost of PCA use in ED varies with the clinical scenario, but is in the region of £15–£25 per hour of moderate or severe pain averted. Overall additional costs are around £20 per 12-hour patient episode.Figure 1 Figure 2